Pneumococcal Encounter With the Blood–Brain Barrier Endothelium - Anil, Anjali; Banerjee, Anirban (Frontiers in Cellular and Infection Microbiology, 2020)
Meningitis, the inflammation of protective membrane surrounding the brain and spinal cord (known as meninges) is a condition associated with high mortality rates and permanent neurological sequelae in a significant proportion of survivors. The opportunistic pathogen Streptococcus pneumoniae (SPN / pneumococcus) is the leading cause of bacterial meningitis in adults and older children. Following infection of the lower respiratory tract and subsequent bloodstream invasion, SPN breaches the blood-brain barrier endothelium for invasion of the central nervous system. Transcytosis, a mode of passage through the endothelial cells has been identified as the predominant route of pneumococcal blood-brain barrier trafficking. Herein, we review the interactions enabling SPN invasion into the brain endothelial cells, events involved in the tug-of-war between pneumococcal virulence factors and host intracellular defence machineries and pneumococcal strategies for evasion of host defences and successful trans-endothelial trafficking.